Afzelia quanzensis bark extract for green synthesis of silver nanoparticles and study of their antibacterial activity - Moyo, Mambo; Gomba, Makore; Nharingo, Tichaona (Springer, 2016)
In the present study, Afzelia quanzensis bark 8 extract was tested for the biosynthesis of silver nanopartiJHJcles (AgNPs). Based on UV-Vis spectrum analysis, the 10 characteristic absorption band was observed at 427 nm. 11 Furthermore, the size and shape of the nanoparticles ranged 12 from 10 to 80 nm and were spherical in shape as observed 13 through SEM analysis. In addition, the X-ray diffraction URBlanalvsis showed that the silver nanoparticles are crystalline 15 in nature and have a face-centred cubic structure. Based on 16 FTIR analysis, the presence of phytochemical functional 17 groups such as carboxyl (-C=0) and amine (N-H) in 18 Afzelia quanzensis bark extract further confirmed the 19 responsible reducing agents for nanoparticles formation. 20 Interestingly, the synthesized silver nanoparticles at 50 mg/ 21 L concentration showed significant antibacterial activity 22 against Escherichia coli and Staphylococcus aureus.